Mekanisme Legislasi dalam Perspektif Hukum Tata Negara: Komparasi Indonesia Inggris - Putri Ayu Ajeng Nina Zuraida; Kaisya Jamilatul Ghofiroh; Mutiara Cemerlang Nitiasa; Nabila Shifa Khairunnisa; Sicilia Sandra Yudisthira (VJJ, 2023)
The legislative mechanism is a crucial factor in Constitutional Law because it serves as a tool for translating political will into binding law. We will compare Indonesia and the Inggris in this study because they have different legal structures and forms of government. Indonesia, as a country with a civil law tradition and a presidential system, places the law-making process within a joint framework between the House of Representatives (DPR) and the President, as stipulated in the 1945 Constitution and Law No. 12 of 2011 in conjunction with Law No. 13 of 2022. Meanwhile, the Inggris, which inherited the common law tradition and a parliamentary system, implements legislation through a bicameral mechanism between the House of Commons and the House of Lords based on the doctrine of parliamentary sovereignty where parliament is positioned as the holder of the highest legal authority. This study uses a normative juridical method to analyze the normative structure and constitutional implementation in both countries. This study uses data derived from primary, secondary, and tertiary legal materials. The results of the study suggest that although both countries have similarities in the application of a bicameral system and the existence of control mechanisms for the quality of legislation, fundamental differences are seen in the legal system, the position of the executive in the legislative process, and the existence or absence of a written constitution as a formal basis. With a comparative approach, this research aims to clarify the theoretical understanding of Indonesian and Inggris legislative regulations as two countries with legislative regulation-making mechanisms that are based on different legal systems. Keywords: Legislation; Comparative Constitutional Law; Presidential-Parliamentary System; Civil Law; Common Law.